2020
DOI: 10.48550/arxiv.2006.05891
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On Noise Injection in Generative Adversarial Networks

Ruili Feng,
Deli Zhao,
Zhengjun Zha

Abstract: Noise injection has been proved to be one of the key technique advances in generating high-fidelity images. Despite its successful usage in GANs, the mechanism of its validity is still unclear. In this paper, we propose a geometric framework to theoretically analyze the role of noise injection in GANs. Based on Riemannian geometry, we successfully model the noise injection framework as fuzzy equivalence on geodesic normal coordinates. Guided by our theories, we find that existing methods are incomplete and a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In particular, KernelGAN-FKP delivers comparable performance in handling image noise. The underlying reason might be that noise injection in the generator of GAN can help to circumvent over-fitting [14].…”
Section: Visual Resultsmentioning
confidence: 99%
“…In particular, KernelGAN-FKP delivers comparable performance in handling image noise. The underlying reason might be that noise injection in the generator of GAN can help to circumvent over-fitting [14].…”
Section: Visual Resultsmentioning
confidence: 99%
“…It is thought that in generative modeling, the generator's intrinsic dimensionality should ideally match that of the real image manifold [33,45]. While the latter is hard to calculate [14], it has been estimated to values as low as 20-50 [16,42]. Yet, training remains effective with our seemingly excessive overparameterization.…”
Section: Discussionmentioning
confidence: 99%
“…Fix 2D noise injection Existing studies (Karras et al, 2019;Feng et al, 2020) have showed that injecting per-pixel noise can increase the model's capability of modeling stochastic variation (e.g. hairs, stubble).…”
Section: Nerf Path Regularizationmentioning
confidence: 99%